Efektivitas Keterampilan Menulis dalam Meningkatkan Kemampuan Berpikir Kritis Siswa Sekolah Dasar di Era Digital - Maria Goreti Rini Kristiantari; Chindytia; Ni Kadek Rina Aryati Sahdewi; Ketut Ayu Mei Wulandari; I Putu Sandhitya Eka Pradana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of digital technology has transformed the way students access and process information, requiring the strengthening of critical thinking skills from an early stage of education. One effective approach to support this development is through writing skills, as writing activities encourage students to organize ideas, analyze information, and construct logical arguments. This study aims to examine the effectiveness of writing skills in improving critical thinking abilities among elementary school students in the digital era. This research employed a quantitative approach using a one group pretest-posttest design. The participants were 30 fifth-grade elementary school students. Data were collected through writing skill tests and critical thinking assessments. The data were analyzed using descriptive statistics and comparative tests to identify differences before and after the treatment. The results indicate a significant improvement in students’ critical thinking skills after the implementation of digital-based writing activities, as reflected in the increase of average scores from pretest to posttest. Therefore, writing skills are proven to be effective in enhancing students’ critical thinking abilities. These findings highlight the importance of integrating writing activities into language learning in alignment with digital advancements.